An overview of patents on therapeutic monoclonal antibodies in Europe: are they a hurdle to biosimilar market entry? - Moorkens, Evelien (MAbs, 2020)
As patents on many high-selling biological medicines are expiring, non-innovator versions, such as biosimilars, may enter this multi-billion dollar market. This study aims to map patents and patent applications for innovator as well as biosimilar monoclonal antibodies in Europe, and investigates legal challenges associated with patenting the innovator product and alleged infringing activities, focusing on consequences for biosimilar developers. Via an exploratory literature review in PubMed and a database analysis in Darts-ip, Derwent Innovation, and Espacenet, an overview of basic patents and exclusivity rights for some of the best-selling biologicals is given, supplemented with a detailed analysis of patents taken during the medicine’s life cycle via three specific case studies (trastuzumab, bevacizumab, cetuximab). Case law was used to determine which patents were viewed by biosimilar developers as blocking market entry. For the selected monoclonal antibodies, the key protection instruments appeared to be the basic patent and the additional protection provided by a supplementary protection certificate. We observed that additional patents filed after the basic patent are hard to obtain and often insufficient in blocking market entry of biosimilars, but can in some cases be a substantial hurdle for biosimilar developers to overcome in patent litigation cases or to invent around, creating uncertainty on the launch date of a biosimilar on the market. These hurdles, however, seem to be surmountable, given that many cases were won by biosimilar developers. Also, biosimilars can be protected by filing new patents and these mainly pertain to new formulations.